Guanaco management in Argentina: Taking a commons perspective - Lichtenstein, Gabriela (2013)
This paper deals with wildlife as a non-conventional common-pool resource (CPR) in a country, Argentina, which is poorly represented in the commons literature. Many of Argentinás public policies regarding natural resource management reflect the historical denial of indigenous and low-income rural communities by the State and the promotion of private property over common property. This paper discusses the challenges facing live shearing programs for guanaco (Lama guanicoe) in Argentinian Patagonia and the potential for incorporating lessons from the commons in order to promote sustainable use.